Schedule - Dental Subscale Dental fear in schoolchildren: a pilot study using the Children’s Fear Survey Schedule - Dental Subscale (Research, Society and Development, 2020)
To estimate the prevalence of dental fear in schoolchildren and verify its association with gender, age group and oral health habits. Cross-sectional study with 44 elementary students from public schools. Data on sociodemographic issues and children's oral health habits were collected and the Children’s Fear Survey Schedule - Dental Subscale (CFSS-DS) questionnaire was applied. Descriptive analysis of the data was performed, Fisher's Exact and U Mann-Whitney tests (p